From Knowledge to Action: Does the Competence to Prepare and Reflect on Instruction Mediate Between Mathematics Teacher Knowledge and the Competence to Act in the Classroom? A Mediation Analysis Vom Wissen zum Handeln: Vermittelt die Kompetenz zur Unterrichtsreflexion zwischen mathematischem Professionswissen und der Kompetenz zum Handeln im Mathematikunterricht? Eine Mediationsanalyse - Jeschke, Colin; Lindmeier, Anke; Heinze, Aiso (Journal für Mathematik-Didaktik, 2021)
Despite university teacher training programs providing more practical experience, novice teachers often find the knowledge they acquire at university to be too theoretical and of little help for instruction. Subject-specific teacher knowledge can often not be used effectively for teacher actions under time pressure, which is required when teaching a subject in the classroom. In teacher education, reflecting on instruction (i.e., analyzing and planning instruction) is seen as an essential activity. Teachers are expected to use the declarative subject-specific knowledge typically learned in teacher preparation programs to anticipate and plan upcoming teaching actions. The underlying assumption is that the ability to reflect on instruction—here defined as reflective competence—positively affects an ability to use subject-specific teacher knowledge to spontaneously act during instruction—here defined as action-related competence. However, there is little quantitative evidence to support this assumption. The present study investigates relationships between declarative subject-specific teacher knowledge (usually acquired at university), reflective competence and action-related competence in a sample of N = 251 pre-service and in-service teachers. The results show substantial positive correlations among subject-specific teacher knowledge, reflective competence and action-related competence. In particular, there is a moderate to high correlation between reflective competence and action-related competence. A direct effect of subject-specific teacher knowledge on action-related competence is partially mediated by reflective competence. A full mediation was found in the subsample of pre-service teachers at university level (n = 116). Implications for research and teacher training are discussed.
CRIS-Team Scopus Importer:2024-10-02
Keywords: Content knowledge; Lesson preparation; Pedagogical content knowledge; Teacher education; Teaching competence; Teaching skills